Positive electrode active material, preparation method thereof, positive electrode plate, secondary battery and electric device
By blending lithium iron phosphate particles of different particle sizes, the powder compaction density of the positive electrode active material is improved, and the problems of low compaction density of the positive electrode sheet and low battery power performance in the prior art are solved, and a battery with high compaction density and high power performance is achieved.
Patent Information
- Application Number
- CN202410027248.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-08
- Publication Date
- 2025-04-18
AI Technical Summary
The primary average particle size of the existing lithium iron phosphate positive electrode active materials is small, resulting in low compaction density of the positive electrode sheet and low battery power performance.
The blending method of the first lithium iron phosphate particles and the second lithium iron phosphate particles is adopted. The primary average particle size of the first lithium iron phosphate particles is 500-3000 nm, and the primary average particle size of the second lithium iron phosphate particles is 120-600 nm. By adjusting the blending ratio and preparation process of the particles, the powder compaction density of the positive electrode active material is improved.
The high compaction density of the positive electrode sheet and the high power performance of the battery are achieved, and the energy density and dynamic performance of the secondary battery are improved.
Smart Images

Figure CN119852394A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of secondary batteries, and in particular to a positive electrode active material, a preparation method thereof, a positive electrode sheet, a secondary battery and an electrical device. Background Art
[0002] As the positive electrode active material of lithium-ion batteries, lithium iron phosphate has rapidly become a global research hotspot due to its abundant resources, low price, environmental friendliness, and stable voltage in two-phase reaction.
[0003] As lithium-ion batteries have achieved tremendous development, higher requirements are placed on the compaction density of the positive electrode sheet containing lithium iron phosphate salt and the power performance of the battery. Summary of the invention
[0004] The present application is made in view of the above-mentioned problems, and its purpose is to provide a positive electrode active material, a preparation method thereof, a positive electrode plate, a secondary battery and an electrical device. The positive electrode plate containing the positive electrode active material has a higher compaction density, and the battery containing the positive electrode plate has a higher power performance.
[0005] In order to achieve the above-mentioned objectives, the first aspect of the present application provides a positive electrode active material, including first lithium iron phosphate salt particles and second lithium iron phosphate salt particles, wherein the primary average particle size of the first lithium iron phosphate salt particles is 500-3000nm, and the primary average particle size of the second lithium iron phosphate salt particles is 120-600nm, and can be optionally 150-480nm.
[0006] The positive electrode sheet containing the positive electrode active material of the present application has a higher compaction density, and the battery containing the positive electrode sheet has a higher power performance.
[0007] In any embodiment, the weight ratio of the first lithium iron phosphate salt particles to the second lithium iron phosphate salt particles is 1:9-9:1, optionally 3:7-7:3.
[0008] When the weight ratio of the first lithium iron phosphate salt particles to the second lithium iron phosphate salt particles is 3:7-7:3, the positive electrode sheet containing the positive electrode active material has a higher compaction density.
[0009] In any embodiment, the first lithium iron phosphate salt particles have a molecular formula Li m1 Fe x1 P y1 O j1 Q1 q1, wherein Q1 includes at least one of Al, Na, K, Mg, Cu, Mn, Cr, Zn, Pb, Ca, Co, Ni, Sr, Nb, V, Ti, B, S, Si, N, F, Cl, Br, 0.95≤m1≤1.15, 0.9≤x1≤1, 0.95≤y1≤1, 3.5≤j1≤4, 0<q1≤0.1, and / or
[0010] The second lithium iron phosphate salt particle has a molecular formula of Li m2 Fe x2 P y2 O j2 Q2 q2 , wherein Q2 includes at least one of Al, Na, K, Mg, Cu, Mn, Cr, Zn, Pb, Ca, Co, Ni, Sr, Nb, V, Ti, B, S, Si, N, F, Cl, and Br, 0.95≤m2≤1.15, 0.9≤x2≤1, 0.95≤y2≤1, 3.5≤j2≤4, and 0≤q2≤0.1.
[0011] In any embodiment, in the first lithium iron phosphate salt particles, Q1 includes at least one of Ti, V, Mg, and Nb, and the content of Ti, V, Mg, and / or Nb is 1000-10000 ppm, optionally 2500-6000 ppm, calculated based on the total weight of the first lithium iron phosphate salt particles.
[0012] In any embodiment, the specific surface area (BET) of the first lithium iron phosphate salt particles is 3 m 2 / g-8m 2 / g.
[0013] In any embodiment, the carbon content of the first lithium iron phosphate salt particles is Cx1 weight %, calculated based on the total weight of the first lithium iron phosphate salt particles, wherein 0.8≤Cx1≤2.0, optionally 1.0≤Cx1≤1.6.
[0014] In any embodiment, a ratio z1 of the specific surface area of the first lithium iron phosphate salt particles to Cx1 satisfies 1.5≤z1≤8.5, and optionally satisfies 3≤z1≤6.
[0015] In any embodiment, the primary average particle size of the first lithium iron phosphate salt particles is 650-2500 nm.
[0016] In any embodiment, the capacity ratio of the first lithium iron phosphate salt particles is η≥88%, where η is defined as:
[0017] A battery using the first lithium iron phosphate salt particles as the positive electrode active material is charged and discharged twice at a constant current rate of 0.1C in the voltage range of 2.0V to 3.75V, and then charged and discharged once at a constant current rate of 1C. In the charge and discharge test at a rate of 1C, the capacity value at a discharge voltage of 3.2V is extracted and recorded as C1, the capacity value extracted and discharged to 2.0V is C2, and η=C1 / C2, wherein the charging process includes constant voltage charging, a constant voltage of 3.75V, and a constant voltage cut-off current of 50μA.
[0018] In any embodiment, the first lithium iron phosphate salt particles satisfy at least one of (a)-(f):
[0019] (a) Dv10 of the first lithium iron phosphate salt particles is ≥ 0.2 μm;
[0020] (b) the Dv50 of the first lithium iron phosphate particles is 0.5-5 μm;
[0021] (c) Dv90 of the first lithium iron phosphate salt particles is ≤10 μm;
[0022] (d) Dv99 of the first lithium iron phosphate salt particles is ≤12 μm;
[0023] (e) The powder compaction density of the first lithium iron phosphate salt under a pressure of 3 tons is ≥ 2.25 g / cm 3 ;
[0024] (f) The powder resistivity of the first lithium iron phosphate salt is less than 60Ω·cm.
[0025] In any embodiment, the specific surface area of the second lithium iron phosphate salt particles is 11m 2 / g-16m 2 / g.
[0026] In any embodiment, the carbon content of the second lithium iron phosphate salt particles is Cx2 weight %, calculated based on the total weight of the second lithium iron phosphate salt particles, wherein 1.2≤Cx2≤1.5.
[0027] In any embodiment, based on the total weight of the second lithium iron phosphate salt particles, the carbon content of the second lithium iron phosphate salt particles is Cx2 weight %, and the ratio z2 of the specific surface area of the second lithium iron phosphate salt particles to Cx2 satisfies 9≤z2≤11.
[0028] In any embodiment, the primary average particle size of the second lithium iron phosphate salt particles is 360-480 nm.
[0029] In any embodiment, the first lithium iron phosphate salt particles are mainly obtained by the following preparation method:
[0030] Providing a raw material containing at least a lithium source, an iron source, a phosphorus source, optionally a carbon film-forming agent, optionally a carbon source, and optionally a modifier, and performing at least two sintering steps, wherein:
[0031] The temperature of the first sintering is 500℃-760℃, and can be 550℃-720℃;
[0032] The temperature of the second sintering is 700°C-800°C, and can be optionally 720°C-780°C.
[0033] In any embodiment, the first lithium iron phosphate salt particles are mainly obtained by the following preparation method:
[0034] Providing raw materials containing at least a lithium source, an iron source, a phosphorus source, a carbon source, a carbon film-forming agent, and a modifier, and performing at least two sintering steps, wherein:
[0035] The carbon content of the material after the first sintering is 0.01 wt%-0.79 wt%, optionally 0.05 wt%-0.4 wt%;
[0036] The carbon content of the material after the second sintering is 0.8 wt % to 2.0 wt %, and can be optionally 1.0 wt % to 1.6 wt %.
[0037] In any embodiment, the preparation method of the first lithium iron phosphate salt particles comprises the following steps:
[0038] The first pulverization is performed after the first sintering, and the second pulverization is performed after the second sintering, wherein:
[0039] The Dv50 of the product after the first pulverization is 300nm-1200nm, and can be optionally 400nm-1100nm;
[0040] The Dv50 of the product after the second pulverization is 500nm-5000nm, and can be optionally 700nm-2500nm.
[0041] A second aspect of the present application provides a positive electrode sheet, which includes the positive electrode active material of the first aspect of the present application.
[0042] In any embodiment, the compaction density of the positive electrode sheet is 2.40 g / cm 3 -2.80g / cm 3 . A higher compaction density is beneficial to improving the energy density of secondary batteries.
[0043] In any embodiment, the positive electrode sheet includes a current collector and one or more positive electrode slurry layers disposed on the current collector, wherein at least one positive electrode slurry layer includes the positive electrode active material of the first aspect of the present application.
[0044] A third aspect of the present application provides a secondary battery, which includes the positive electrode sheet of the second aspect of the present application.
[0045] A fourth aspect of the present application provides an electrical device, comprising the secondary battery of the third aspect of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] Figure 1 It is a slice diagram of the positive electrode piece of Example 19 of the present application, wherein the left picture is a slice diagram of the positive electrode piece at a magnification of 5k times, and the right picture is a slice diagram of the positive electrode piece at a magnification of 10k times, observed under SEM (scanning electron microscope).
[0047] Figure 2 is a schematic diagram of a secondary battery according to one embodiment of the present application.
[0048] Figure 3 yes Figure 2 An exploded view of a secondary battery according to an embodiment of the present application is shown.
[0049] Figure 4 is a schematic diagram of a battery module according to an embodiment of the present application.
[0050] Figure 5 It is a schematic diagram of a battery pack according to one embodiment of the present application.
[0051] Figure 6 yes Figure 5 An exploded view of a battery pack according to an embodiment of the present application is shown.
[0052] Figure 7 FIG. 1 is a schematic diagram of an electric device using a secondary battery according to an embodiment of the present application as a power source.
[0053] Figure 8 This is a scanning electron microscope image of the first lithium iron phosphate salt particles with the primary particle size marked according to one embodiment of the present application.
[0054] Description of reference numerals:
[0055] 1 battery pack; 2 upper box; 3 lower box; 4 battery module; 5 secondary battery; 51 shell; 52 electrode assembly; 53 top cover assembly DETAILED DESCRIPTION
[0056] Below, the embodiments of the positive electrode active material and its manufacturing method, positive electrode sheet, secondary battery and electrical device of the present application are specifically disclosed with appropriate reference to the drawings. However, there are cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structure are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0057] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0058] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0059] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0060] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0061] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.
[0062] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0063] As the positive electrode active material of lithium-ion batteries, lithium iron phosphate has rapidly become a global research hotspot due to its abundant resources, low price, environmental friendliness, and stable voltage in two-phase reaction.
[0064] However, the primary average particle size of the existing lithium iron phosphate salt is small, and the positive electrode sheet using the lithium iron phosphate salt alone as the positive electrode active material has a low compaction density, and the battery containing the positive electrode sheet has a low power performance. Therefore, it is necessary to provide a positive electrode active material, and the positive electrode sheet containing the positive electrode active material has a high compaction density, and the battery containing the positive electrode sheet has a high power performance.
[0065] Although the mechanism is not clear, the applicant unexpectedly discovered that in order to achieve high compaction density, lithium iron phosphate salt needs to contain some large particles at the micron level. However, the method of preparing large particles, small particles and micropowders in one step sintering at the same time has different surface energies between micropowders, small particles and large particles during the sintering process, and has different adsorption capacities for carbon sources, which makes it difficult to achieve uniform coating of all particles. At the same time, particles of different sizes have different temperature tolerances. In the process of promoting the growth of large particles, small particles will be over-sintered, resulting in problems such as low power performance and high magnetic substances.
[0066] Based on this, the present application proposes a technical solution to solve the above technical problems.
[0067] [Positive electrode active material]
[0068] The first aspect of the present application provides a positive electrode active material, including first lithium iron phosphate salt particles and second lithium iron phosphate salt particles, wherein the first lithium iron phosphate salt particles have an average primary particle size of 500-3000nm, and the second lithium iron phosphate salt particles have an average primary particle size of 120-600nm, and can be optionally 150-480nm.
[0069] The positive electrode active material of the present application achieves dense filling of the pores between the first lithium iron phosphate salt particles by the second lithium iron phosphate salt particles by mixing the first lithium iron phosphate salt particles with a larger primary average particle size and the second lithium iron phosphate salt particles with a smaller primary average particle size, so that the powder compaction density of the positive electrode active material is relatively high, thereby achieving a positive electrode plate containing the positive electrode active material with a higher compaction density, and the battery containing the positive electrode plate has a higher power performance.
[0070] When the primary average particle size of the second lithium iron phosphate salt particles is 150-480 nm, the positive electrode sheet containing the positive electrode active material has a higher compaction density through denser filling.
[0071] By making the primary average particle size of the first lithium iron phosphate salt particles 500nm-3000nm, the particles can be kept at a suitable micron-level size, thereby avoiding the interface side reactions and processing difficulties caused by nano-sizing the particles, and the particles will not be limited by excessive size and thus have reduced dynamic performance; in addition, it is beneficial to the stirring of the slurry containing the lithium iron phosphate salt particles and the increase of the solid content, thereby improving the processing problems of the battery cell and further increasing the volume energy density of the battery.
[0072] In this application, the term "primary average particle size" refers to the average of the primary particle sizes of all particles, wherein the primary particle size refers to the longest distance between two points on the edge in the cross-sectional view. Figure 8 As shown in the scanning electron microscope image of the first lithium iron phosphate salt particle, the line segment marked by the double arrows in the particle is the primary particle size defined in this application.
[0073] In some embodiments, the first lithium iron phosphate salt particles are primary particles.
[0074] In this article, "primary particles" refer to particles that do not have obvious agglomeration interfaces in the particle scanning electron microscope image, but may have tiny pores and point or line defects, which are different from powder particles that are the smallest units without structures such as stacking and flocculation.
[0075] In some embodiments, the first lithium iron phosphate salt particles are single crystal particles and / or polycrystalline particles.
[0076] In this article, the term "single crystal" refers to a crystal with a complete structure grown from a single crystal nucleus. The single crystal of the present application is a whole under the field of view of a transmission electron microscope photograph, and there is no grain boundary in the single crystal.
[0077] In some embodiments, the single crystal of the present application may have tiny defects, for example, micropores inside, a small number of points and surfaces, or a small number of particles adhering to each other on the surface of a particle.
[0078] As used herein, the term "polycrystalline" refers to a crystal composed of small single crystal particles randomly oriented together, with grain boundaries existing within the polycrystalline.
[0079] In some embodiments, based on the total number of particles of the first lithium iron phosphate salt particles, the number of single crystal particles accounts for greater than or equal to 90%, which is beneficial for reducing BET and improving processing performance.
[0080] In some embodiments, the primary average particle size of the first lithium iron phosphate salt particles may be 650-2500 nm.
[0081] In some embodiments, the primary average particle size of the first lithium iron phosphate salt particles can be 500nm, 550nm, 600nm, 650nm, 700nm, 730nm, 750nm, 780nm, 800nm, 830nm, 850nm, 870nm, 900nm, 950nm, 1000nm, 1100nm, 1200nm, 1300nm, 1400nm, 1500nm, 2000nm, 2100nm, 2200nm, 2300nm, 2400nm, 2500nm, 2600nm, 2700nm, 2800nm, 2900nm, 3000nm, or a range consisting of any two of the above average particle sizes or a value in the range.
[0082] The primary average particle size of the lithium iron phosphate salt particles can be measured by methods and equipment known in the art. For example, it can be tested by scanning electron microscopy and long diameter statistical method. As an example, an argon ion beam is used to cut the pole piece perpendicular to the large surface of the positive electrode pole piece to expose the cross section, and the cross section is photographed by a scanning electron microscope. The particle size of the positive electrode active layer containing lithium iron phosphate salt particles is statistically analyzed by the long diameter statistical method. Specifically, the total number of lithium iron phosphate salt particles with a primary particle size greater than 50nm and the primary particle size of lithium iron phosphate salt particles with a primary particle size greater than 50nm can be counted in the electron microscope scanning photo. The primary average particle size of the lithium iron phosphate salt particles = the primary particle size of the total lithium iron phosphate salt particles / the total number of lithium iron phosphate salt particles. In the primary particle size statistical process, particles with a primary particle size of 0 < ≤ 50nm are not within the statistical range.
[0083] In some embodiments, the primary average particle size of the first lithium iron phosphate salt particles is greater than the primary average particle size of the second lithium iron phosphate salt particles. In some embodiments, the primary average particle size of the first lithium iron phosphate salt particles is greater than the primary average particle size of the second lithium iron phosphate salt particles, and the difference between the two may be 100nm to 2880nm. In some embodiments, the primary average particle size of the first lithium iron phosphate salt particles is greater than the primary average particle size of the second lithium iron phosphate salt particles, and the difference between the two may be 100nm to 2700nm. In some embodiments, the primary average particle size of the first lithium iron phosphate salt particles is greater than the primary average particle size of the second lithium iron phosphate salt particles, and the difference between the two may be 140nm to 2640nm.
[0084] In some embodiments, the primary average particle size of the first lithium iron phosphate salt particles is greater than the primary average particle size of the second lithium iron phosphate salt particles, and the difference between the two can be 140nm, 270nm, 290nm, 390nm, 420nm, 510nm, 660nm, 720nm, 750nm, 2140nm, 2640nm, or a range consisting of any two of the above differences or a value in the range.
[0085] In some embodiments, the weight ratio of the first lithium iron phosphate salt particles to the second lithium iron phosphate salt particles is 1:9-9:1, optionally 3:7-7:3.
[0086] When the weight ratio of the first lithium iron phosphate salt particles to the second lithium iron phosphate salt particles is 3:7-7:3, by adjusting the blending ratio of the first lithium iron phosphate salt particles with a larger primary average particle size and the second lithium iron phosphate salt particles with a smaller primary average particle size, a denser filling of the pores between the first lithium iron phosphate particles by the second lithium iron phosphate salt particles is achieved, resulting in a higher powder compaction density of the positive electrode active material, thereby achieving a higher compaction density of the positive electrode electrode sheet containing the positive electrode active material.
[0087] In some embodiments, the weight ratio of the first lithium iron phosphate salt particles to the second lithium iron phosphate salt particles is 3:7-9:1.
[0088] When the weight ratio of the first lithium iron phosphate salt particles to the second lithium iron phosphate salt particles is 3:7-9:1, the proportion of the first lithium iron phosphate salt particles is increased, and the first lithium iron phosphate salt particles have a smaller specific surface area and less solvent adsorption for the slurry, so that the positive electrode slurry containing the positive electrode active material has a higher solid content. At the same time, by increasing the weight ratio of the first lithium iron phosphate salt particles, the number of the first lithium iron phosphate salt particles increases, and the capacity proportion η of the overall material discharged to 3.2V increases accordingly, so that the battery containing the positive electrode active material has a higher η value, and the battery containing the positive electrode active material has a lower DCR (10% SOC), reflecting that the battery has better kinetic performance and higher power performance.
[0089] In this application, the term "DCR (10% SOC)" refers to the direct current resistance (DCR) when the state of charge (SOC) is 10%. This parameter can characterize the power performance of the battery. The lower the DCR (10% SOC), the better the power performance of the battery.
[0090] In some embodiments, the weight ratio of the first lithium iron phosphate salt particles to the second lithium iron phosphate salt particles is 4:6-9:1.
[0091] When the weight ratio of the first lithium iron phosphate salt particles to the second lithium iron phosphate salt particles is 4:6-9:1, the proportion of the first lithium iron phosphate salt particles is increased, and the first lithium iron phosphate salt particles have a smaller specific surface area and less solvent adsorption for the slurry, so that the positive electrode slurry containing the positive electrode active material has a higher solid content. At the same time, by increasing the weight ratio of the first lithium iron phosphate salt particles, the number of the first lithium iron phosphate salt particles increases, and the capacity proportion η of the overall material discharged to 3.2V increases accordingly, so that the battery containing the positive electrode active material has a higher η value, and the battery containing the positive electrode active material has a lower DCR (10% SOC), reflecting that the battery has better kinetic performance and higher power performance.
[0092] In some embodiments, the weight ratio of the first lithium iron phosphate salt particles to the second lithium iron phosphate salt particles is 7:3-9:1.
[0093] When the weight ratio of the first lithium iron phosphate salt particles to the second lithium iron phosphate salt particles is 7:3-9:1, the proportion of the first lithium iron phosphate salt particles is increased, and the first lithium iron phosphate salt particles have a smaller specific surface area and less solvent adsorption for the slurry, so that the positive electrode slurry containing the positive electrode active material has a higher solid content. At the same time, by increasing the weight ratio of the first lithium iron phosphate salt particles, the number of the first lithium iron phosphate salt particles increases, and the capacity proportion η of the overall material discharged to 3.2V increases accordingly, so that the battery containing the positive electrode active material has a higher η value, and the battery containing the positive electrode active material has a lower DCR (10% SOC), reflecting that the battery has better kinetic performance and higher power performance.
[0094] In some embodiments, the first lithium iron phosphate salt particles have a molecular formula of Li m1 Fe x1 P y1 O j1 Q1 q1 , wherein Q1 includes at least one of Al, Na, K, Mg, Cu, Mn, Cr, Zn, Pb, Ca, Co, Ni, Sr, Nb, V, Ti, B, S, Si, N, F, Cl, Br, 0.95≤m1≤1.15, 0.9≤x1≤1, 0.95≤y1≤1, 3.5≤j1≤4, 0<q1≤0.1, and / or
[0095] The second lithium iron phosphate salt particle has a molecular formula of Li m2 Fe x2 P y2 O j2 Q2 q2 , wherein Q2 includes at least one of Al, Na, K, Mg, Cu, Mn, Cr, Zn, Pb, Ca, Co, Ni, Sr, Nb, V, Ti, B, S, Si, N, F, Cl, and Br, 0.95≤m2≤1.15, 0.9≤x2≤1, 0.95≤y2≤1, 3.5≤j2≤4, and 0≤q2≤0.1.
[0096] In some embodiments, the first lithium iron phosphate salt particles have a molecular formula of Li m1 Fe x1 P y1 O j1 Q q1, m1 can be 0.95, 0.98, 1.00, 1.03, 1.05, 1.08, 1.10, 1.13, 1.15, x1 can be 0.9, 1.0, y1 can be 0.95, 0.98, 1.00, 1.03, 1.05, 1.08, 1.10, 1.13, 1.15, j1 can be 3.5, 3.6, 3.7, 3.8, 3.9, 4, and q1 can be 0, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1.
[0097] In some embodiments, the second lithium iron phosphate salt particles have a molecular formula of Li m2 Fe x2 P y2 O j2 Q q2 , m2 can be 0.95, 0.98, 1.00, 1.03, 1.05, 1.08, 1.10, 1.13, 1.15, x2 can be 0.9, 1.0, y2 can be 0.95, 0.98, 1.00, 1.03, 1.05, 1.08, 1.10, 1.13, 1.15, j2 can be 3.5, 3.6, 3.7, 3.8, 3.9, 4, and q2 can be 0, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1.
[0098] Modifying the first lithium iron phosphate salt particles and / or the second lithium iron phosphate salt particles by Q1 and / or Q2 elements helps to improve the ion transport capacity of the positive electrode active material. The above elements can create vacancies in the particle lattice or change the interatomic bond length, facilitating the movement of lithium ions in the lattice, thereby effectively improving the conductivity of the particles themselves and improving the kinetic properties of the positive electrode active material. In the present application, the modification can be specifically manifested as doping and / or coating.
[0099] In some embodiments, in the first lithium iron phosphate salt particles, Q1 includes at least one of Ti, V, Mg, and Nb, and the content of Ti, V, Mg, and / or Nb is 1000-10000 ppm, optionally 2500-6000 ppm, calculated based on the total weight of the first lithium iron phosphate salt particles.
[0100] In some embodiments, based on the total weight of the first lithium iron phosphate salt particles, the content of Q1 in the first lithium iron phosphate salt particles is 1000ppm, 2000ppm, 2500ppm, 3000ppm, 3500ppm, 4000ppm, 4500ppm, 5000ppm, 5500ppm, 6000ppm, 6500ppm, 7000ppm, 7500ppm, 8000ppm, 8500ppm, 9000ppm, 9500ppm, 10000ppm, or a range consisting of any two of the above Q1 contents or a value within the range.
[0101] The content of Q1 in the lithium iron phosphate salt particles, for example, the content of Ti, can be measured by methods and equipment known in the art. For example, the test can be performed with reference to GB / T 33822-2017.
[0102] The content of modifying elements in existing lithium iron phosphate salt particles is generally low or no modifying elements are added. Increasing the content of Q1 element in the first lithium iron phosphate salt particles helps to further improve the bulk ion transport capacity of the first lithium iron phosphate salt particles and improve its kinetic performance. However, as the content of Q1 element further increases, the bulk ion transport capacity may not continue to increase, and it may also occupy the position of lithium ions, affecting the performance of gram capacity. The range of Q1 element in this application helps to further obtain better kinetic performance and gram capacity.
[0103] In some embodiments, in the first lithium iron phosphate salt particles, Q1 includes Ti, and the content of Ti is 1000-10000 ppm, optionally 2500-6000 ppm, calculated based on the total weight of the first lithium iron phosphate salt particles.
[0104] In some embodiments, in the first lithium iron phosphate salt particles, Q1 includes V, and the content of V is 1000-10000 ppm, optionally 2500-6000 ppm, calculated based on the total weight of the first lithium iron phosphate salt particles.
[0105] In some embodiments, in the first lithium iron phosphate salt particles, Q1 includes Nb, and the content of Nb is 1000-10000 ppm, optionally 2500-6000 ppm, calculated based on the total weight of the first lithium iron phosphate salt particles.
[0106] In some embodiments, in the first lithium iron phosphate salt particles, Q1 includes Ti, and the content of Ti is 5000-6000 ppm, calculated based on the total weight of the first lithium iron phosphate salt particles.
[0107] Calculated based on the total weight of the first lithium iron phosphate salt particles, when the Ti content in the first lithium iron phosphate salt particles is 5000-6000ppm, by further appropriately increasing the Ti element content in the first lithium iron phosphate salt particles, it helps to further improve the bulk ion transport capacity of the first lithium iron phosphate salt particles, so that the battery containing the positive electrode active material has a higher η value, and the battery containing the positive electrode active material has a lower DCR (10% SOC), reflecting that the battery has better kinetic performance and higher power performance.
[0108] In some embodiments, the specific surface area of the first lithium iron phosphate salt particles is 3 m 2 / g-8m 2 / g.
[0109] In some embodiments, the specific surface area BET of the first lithium iron phosphate salt particles may be 3 m 2 / g, 3.5m 2 / g, 4m 2 / g, 4.5m 2 / g, 5m 2 / g, 5.5m 2 / g, 5.98m 2 / g, 6m 2 / g, 6.5m 2 / g, 7m 2 / g, 7.5m 2 / g, 8m 2 / g, or is a range of the specific surface area BET composition of any two of the above-mentioned first lithium iron phosphate salt particles or a value within the range.
[0110] In the present application, the term "specific surface area" or "BET" refers to the total area per unit mass of particles. In the present application, the BET of lithium iron phosphate particles is related to factors such as the primary average particle size of the lithium iron phosphate particles, the carbon content, the density of the carbon coating, the degree of fit between the carbon and the particles, and the looseness and porosity of the particles.
[0111] The BET specific surface area of the particles can be measured by methods and equipment known in the art. For example, it can be tested according to the gas adsorption method with reference to GB / T 19587-2017. As an example, lithium iron phosphate particles are taken as samples and placed in a sample tube, the sample tube is immersed in liquid nitrogen at -196°C, and the adsorption amount of nitrogen on the solid surface at different pressures is measured at a relative pressure of 0.05-0.30. The sample monolayer adsorption amount is obtained based on the BET multilayer adsorption theory and its formula, thereby obtaining the specific surface area of the sample.
[0112] The BET of the first lithium iron phosphate salt particles is controlled at 3m 2 / g-8m 2 / g, which is conducive to further balancing the processing performance of the positive electrode slurry and the improvement of the solid content, thereby improving the processing problems of the battery cell and further increasing the volume energy density of the battery.
[0113] In some embodiments, the specific surface area of the first lithium iron phosphate salt particles is 6 m 2 / g-8m 2 / g.
[0114] When the specific surface area of the first lithium iron phosphate salt particles is 6m 2 / g-8m 2 / g, by balancing the processing properties of the positive electrode slurry, the battery containing the positive electrode active material has a higher η value, and the battery containing the positive electrode active material has a lower DCR (10% SOC), which reflects that the battery has better kinetic performance and higher power performance.
[0115] In some embodiments, the carbon content of the first lithium iron phosphate salt particles is Cx1 wt % calculated based on the total weight of the first lithium iron phosphate salt particles, wherein 0.8≤Cx1≤2.0, optionally 1.0≤Cx1≤1.6.
[0116] Increasing the carbon content of the first lithium iron phosphate salt particles helps to improve its electrical conductivity, thereby improving the kinetic performance and gram capacity. The carbon content range of the present application helps to further obtain better kinetic performance and gram capacity.
[0117] In some embodiments, the carbon content of the first lithium iron phosphate salt particles is Cx1 weight %, calculated based on the total weight of the first lithium iron phosphate salt particles, wherein 0.8≤Cx1≤1.4.
[0118] In some embodiments, based on the total weight of the first lithium iron phosphate salt particles, the carbon content of the first lithium iron phosphate salt particles is 0.8 weight%, 0.9 weight%, 1.0 weight%, 1.1 weight%, 1.2 weight%, 1.3 weight%, 1.4 weight%, 1.5 weight%, 1.6 weight%, 1.7 weight%, 1.8 weight%, 1.9 weight%, 2.0 weight%, or a range consisting of any two of the above carbon contents or a value within the range.
[0119] In some embodiments, the carbon content of the first lithium iron phosphate salt particles is Cx1 wt % calculated based on the total weight of the first lithium iron phosphate salt particles, wherein 1.2≤Cx1≤1.4.
[0120] When 1.2≤Cx1≤1.4, increasing the carbon content of the first lithium iron phosphate salt particles helps to improve the conductivity of the first lithium iron phosphate salt particles and the positive electrode active material containing the same, so that the battery containing the positive electrode active material has a higher η value, and the battery containing the positive electrode active material has a lower DCR (10% SOC), reflecting that the battery has better kinetic performance and higher power performance.
[0121] In some embodiments, the carbon contained in the first lithium iron phosphate salt particles is coated on the surface of the particles. In some embodiments, the carbon contained in the first lithium iron phosphate salt particles is embedded in the particles. In some embodiments, the carbon contained in the first lithium iron phosphate salt particles is partially coated on the surface of the particles and partially embedded in the particles.
[0122] In some embodiments, a ratio z1 of the specific surface area of the first lithium iron phosphate salt particle to Cx1 satisfies 1.5≤z1≤8.5, and optionally satisfies 3≤z1≤6.
[0123] In some embodiments, a ratio z1 of the specific surface area of the first lithium iron phosphate salt particle to Cx1 satisfies 3≤z1≤6, and optionally satisfies 3.5≤z1≤6.
[0124] In some embodiments, z1 can be 1.5, 1.8, 2, 2.3, 2.5, 2.8, 3, 3.2, 3.5, 3.75, 3.8, 4, 4.17, 4.3, 4.5, 4.58, 4.8, 4.98, 5, 5.3, 5.42, 5.5, 5.71, 5.8, 5.83, 6, 6.3, 6.5, 6.8, 7, 7.3, 7.5, 7.8, 8, 8.3, 8.5, or a range consisting of any two of the above z1 values or a value within the range.
[0125] The ratio z1 of the specific surface area BET of the first lithium iron phosphate salt particle to Cx1 can characterize the uniform density of the carbon contained in the first lithium iron phosphate salt particle. When the primary average particle size and carbon content of the first lithium iron phosphate salt particle remain unchanged, the lower the ratio z1, the higher the carbon coating utilization rate in the particle, the less floating carbon, and the more uniform and dense the carbon contained in the first lithium iron phosphate salt particle. Improving the uniform density of the contained carbon is conducive to further improving the kinetic performance and gram capacity of the first lithium iron phosphate salt particle, but too high carbon density may affect the insertion and extraction of lithium ions, and to a certain extent affect the kinetic performance and gram capacity of the secondary battery. The range of the ratio z1 of the present application is conducive to the carbon contained in the first lithium iron phosphate salt particle having a suitable uniform density, which is conducive to improving the conductivity of the particle surface, and is conducive to further improving the gram capacity and kinetic performance of the secondary battery.
[0126] In some embodiments, the capacity ratio of the first lithium iron phosphate salt particles is η≥88%, where η is defined as:
[0127] A battery using the first lithium iron phosphate salt particles as the positive electrode active material is charged and discharged twice at a constant current rate of 0.1C in the voltage range of 2.0V to 3.75V, and then charged and discharged once at a constant current rate of 1C. In the charge and discharge test at a rate of 1C, the capacity value at a discharge voltage of 3.2V is extracted as C1, and the capacity value at a discharge voltage of 2.0V is extracted as C2, η=C1 / C2, wherein the charging process includes constant voltage charging, a constant voltage of 3.75V, and a constant voltage cut-off current of 50μA.
[0128] In some embodiments, η can be 88%, 89%, 90%, 91%, 92%, 93%, 94%, 95%, or a range consisting of any two of the above η values or a value within the range.
[0129] The η value of the first lithium iron phosphate salt particles can be measured by methods and equipment known in the art. As an example, a button battery is first prepared. The specific button battery preparation process is: 2.0000g of the first lithium iron phosphate salt particles are mixed with 0.1111g of conductive carbon black and 0.1111g of polyvinylidene fluoride, and then added to 2.5g of organic solvent N-methylpyrrolidone, and mixed thoroughly to form a slurry. The slurry is coated on aluminum foil with a coating thickness of 140 microns, vacuum dried at 120°C for 2h, and punched into a disc with a diameter of 13mm using a puncher. Use a tablet press to press the tablet at 10Mpa, and vacuum insulate at 120°C for 12h to obtain a positive electrode. Weigh the weight of the positive electrode, where the loading amount of the lithium iron phosphate salt particles is 11-12mg. Button cells were assembled in an argon-protected glove box, with a metal lithium sheet as the negative electrode, an electrolyte of a 1:1 volume ratio of EC (ethylene carbonate) and DMC (1,2-dimethyl carbonate) mixed solvent, LiPF6 electrolyte, and a Celgard 2400 microporous polyethylene membrane as the separator.
[0130] The prepared button cell was tested for electrical performance on a blue electric tester. Specifically, the button cell was charged and discharged twice at a constant current of 0.1C within a voltage range of 2.0V to 3.75V, and then charged and discharged once at a constant current of 1C. In the charge and discharge test at a rate of 1C, the capacity value extracted when the discharge voltage was 3.2V was recorded as C1, and the capacity value extracted when discharged to 2.0V was recorded as C2, and η = C1 / C2. The charging process includes constant voltage charging, constant voltage of 3.75V, and constant voltage cut-off current of 50μA.
[0131] The capacity ratio η of the first lithium iron phosphate salt particles can reflect its kinetic performance and platform retention performance, which can be adjusted by adjusting the primary average particle size, carbon content, carbon source and carbon film-forming agent ratio, modifier and its content of the first lithium iron phosphate salt particles. The η value of the first lithium iron phosphate salt particles of the present application is ≥88%, which has good kinetic performance. At the same time, when the η value is high, the secondary battery can still maintain good power performance when discharged to a low state of charge (SOC), that is, the battery with a high η value has a small voltage drop value when discharged at a low power and high current.
[0132] In some embodiments, the primary average particle size of the second lithium iron phosphate salt particles is 150-480 nm.
[0133] In some embodiments, the primary average particle size of the second lithium iron phosphate salt particles is 120 nm, 150 nm, 210 nm, 360 nm, 450 nm, 480 nm, 600 nm, or a range consisting of any two of the foregoing primary average particle sizes or a value within the range.
[0134] In some embodiments, the primary average particle size of the second lithium iron phosphate salt particles is 360-480 nm.
[0135] In some embodiments, the specific surface area of the second lithium iron phosphate salt particles is 11 m 2 / g-16m 2 / g, optional 11.8m 2 / g-15.5m 2 / g.
[0136] In some embodiments, the specific surface area of the second lithium iron phosphate salt particles is 11.8 m 2 / g, 12.1m 2 / g, 12.5m 2 / g, 12.8m 2 / g, 14.9m 2 / g, 14.0m 2 / g, 15.5m 2 / g, or a range consisting of any two of the above specific surface areas or a value within the range.
[0137] If the BET of the second lithium iron phosphate salt particles is too high, the particles will absorb more water and affect the processing performance of the mixed positive electrode slurry. However, if the BET of the second lithium iron phosphate salt particles is too low, its gram capacity will be reduced. The BET of the second lithium iron phosphate salt particles is controlled at 11m 2 / g-16m 2 / g, which is beneficial to further balance the processing performance of the positive electrode slurry and the gram capacity of the secondary battery.
[0138] In some embodiments, the carbon content of the second lithium iron phosphate salt particles is Cx2 wt %, calculated based on the total weight of the second lithium iron phosphate salt particles, wherein 1.2≤Cx2≤1.5, optionally 1.2≤Cx2≤1.45.
[0139] In some embodiments, based on the total weight of the second lithium iron phosphate salt particles, the carbon content of the second lithium iron phosphate salt particles is 1.2 wt%, 1.25 wt%, 1.3 wt%, 1.35 wt%, 1.4 wt%, 1.45 wt%, 1.5 wt%, or a range consisting of any two of the above carbon contents or a value within the range.
[0140] In some embodiments, the carbon contained in the second lithium iron phosphate salt particles is coated on the surface of the particles. In some embodiments, the carbon contained in the second lithium iron phosphate salt particles is embedded in the particles. In some embodiments, the carbon contained in the second lithium iron phosphate salt particles is partially coated on the surface of the particles and partially embedded in the particles.
[0141] In some embodiments, a ratio z2 of the specific surface area of the second lithium iron phosphate salt particles to Cx2 satisfies 9≤z2≤11, optionally 9.85≤z2≤10.64.
[0142] In some embodiments, the ratio z2 of the specific surface area of the second lithium iron phosphate salt particles to Cx2 is 9, 9.5, 9.85, 10.00, 10.08, 10.42, 10.64, 11, or a range consisting of any two of the above z2 or a value within the range.
[0143] In some embodiments, the first lithium iron phosphate salt particles satisfy at least one of (a)-(f):
[0144] (a) Dv10 of the first lithium iron phosphate salt particles is ≥ 0.2 μm;
[0145] (b) the Dv50 of the first lithium iron phosphate particles is 0.5-5 μm;
[0146] (c) Dv90 of the first lithium iron phosphate salt particles is ≤10 μm;
[0147] (d) Dv99 of the first lithium iron phosphate salt particles is ≤12 μm;
[0148] (e) The powder compaction density of the first lithium iron phosphate salt under a pressure of 3 tons is ≥ 2.25 g / cm 3 ;
[0149] (f) The powder resistivity of the first lithium iron phosphate salt is less than 60Ω·cm.
[0150] As used herein, the term "Dv10" refers to the particle size corresponding to the particle volume cumulative particle size distribution percentage reaching 10%.
[0151] As used herein, the term "Dv90" refers to the particle size at which the volume cumulative particle size distribution percentage in the particles reaches 90%.
[0152] As used herein, the term "Dv99" refers to the particle size corresponding to the 99% cumulative particle size distribution percentage in the particles.
[0153] In this article, the term "powder compaction density" refers to the density of a compact with a certain density and strength formed when the powder moves and deforms during the external compression process, larger gaps are filled, the contact area between particles increases, the attraction between atoms is generated, and the mechanical fit between particles is enhanced. The unit is g / cm 3 .
[0154] In some embodiments, the first lithium iron phosphate salt particles have a Dv10<Dv50.
[0155] In some embodiments, the first lithium iron phosphate salt particles have a Dv90>Dv50.
[0156] In some embodiments, the Dv50 of the first lithium iron phosphate particles can be 500nm, 600nm, 700nm, 800nm, 900nm, 1000nm, 1100nm, 1200nm, 1300nm, 1400nm, 1500nm, 1700nm, 1900nm, 2000nm, 2300nm, 2500nm, 2700nm, 2900nm, 3000nm, 3200nm, 3400nm, 3600nm, 3800nm, 4000nm, 4200nm, 4400nm, 4600nm, 4800nm, 5000nm, or a range composed of the Dv50 of any two of the above second crushing products or a value within this range.
[0157] The Dv10, Dv50, Dv90 and Dv99 of the first lithium iron phosphate salt particles can be measured by methods and equipment known in the art. For example, it can be measured with reference to GB / T19077.1-2016 using a laser particle size analyzer (Malvern MasterSize 3000).
[0158] Under different pressures, the powder compaction density of the first lithium iron phosphate salt particles can be measured by methods and equipment known in the art. For example, it can be measured by using a compaction density instrument with reference to GB / T 24533-2009. Specifically, a certain amount of lithium iron phosphate salt particles are placed on a special compaction mold (the mold diameter is known), and the mold is hollow in the middle and has a metal disc above and below. The lithium iron phosphate salt particles are placed between the metal discs, a metal cylinder is placed on the top, and the mold is placed on the compaction density instrument. Different pressures (for example, 3T) can be set. The thickness of the lithium iron phosphate salt particles under different pressures can be read on the device. The powder compaction density of the lithium iron phosphate salt particles is ρ=m / v, where v=(S×H), m is the mass of the lithium iron phosphate salt particles, S is the bottom area of the mold, and H is the thickness of the lithium iron phosphate salt particles after compaction.
[0159] The powder resistivity of the first lithium iron phosphate salt particles can be measured by methods and equipment known in the art. For example, GB / T 33822-2017 can be referred to and a powder resistivity meter (Suzhou Jingge, ST2722 model) can be used for measurement. Specifically, a certain amount of lithium iron phosphate salt particles (for example, 1 g) is weighed and added to the feeding chamber of the powder resistivity meter, and a pressure of 8 MPa is applied to test the forward resistivity and reverse resistivity of the lithium iron phosphate salt particles respectively, and the average value of the two is taken as the powder resistivity of the lithium iron phosphate salt particles.
[0160] By making the first lithium iron phosphate salt particles satisfy at least one of (a)-(f), the first lithium iron phosphate salt particles can better achieve the technical effect of the present application.
[0161] In some embodiments, the first lithium iron phosphate salt particles are mainly obtained by the following preparation method:
[0162] Providing a raw material containing at least a lithium source, an iron source, a phosphorus source, optionally a carbon film-forming agent, optionally a carbon source, and optionally a modifier, and performing at least two sintering steps, wherein:
[0163] The temperature of the first sintering is 500℃-760℃, and can be 550℃-720℃;
[0164] The temperature of the second sintering is 700°C-800°C, and can be optionally 720°C-780°C.
[0165] In some embodiments, the temperature of the first sintering may be 500°C, 530°C, 550°C, 580°C, 600°C, 630°C, 650°C, 680°C, 700°C, 710°C, 720°C, 730°C, 740°C, 750°C, 760°C, or a range consisting of any two of the above first sintering temperatures or a value in this range; the temperature of the second sintering may be 700°C, 710°C, 720°C, 730°C, 740°C, 750°C, 760°C, 770°C, 780°C, 790°C, 800°C, or a range consisting of any two of the above second sintering temperatures or a value in this range.
[0166] In some embodiments, the heating rates of the first sintering and the second sintering are independently 2° C. / min-20° C. / min.
[0167] In some embodiments, the heating rates in the first sintering and the second sintering are each independently 2°C / min, 5°C / min, 7°C / min, 10°C / min, 13°C / min, 15°C / min, 17°C / min or 20°C / min.
[0168] In some embodiments, the constant temperature sintering time of the first sintering is 1-6 hours. In some embodiments, the constant temperature sintering time of the first sintering can be 1 hour, 1.5 hours, 2 hours, 2.5 hours, 3 hours, 3.5 hours, 4 hours, 4.5 hours, 5 hours, 5.5 hours or 6 hours.
[0169] In some embodiments, the constant temperature sintering time of the second sintering is 2-12 hours. In some embodiments, the constant temperature sintering time of the second sintering can be 1 hour, 1.5 hours, 2 hours, 2.5 hours, 3 hours, 3.5 hours, 4 hours, 4.5 hours, 5 hours, 5.5 hours, 6 hours, 6.5 hours, 7 hours, 7.5 hours, 8 hours, 8.5 hours, 9 hours, 9.5 hours, 10 hours, 10.5 hours, 11 hours, 11.5 hours or 12 hours.
[0170] Compared to the traditional preparation method that uses high temperature to achieve particle growth, the first lithium iron phosphate salt particles of the embodiment of the present application are sintered twice, and controlling the temperature of the two sinterings is conducive to preparing the first lithium iron phosphate salt particles having the primary average particle size and specific surface area of the present application. Furthermore, controlling the heating rate, sintering temperature and constant temperature sintering time of the first sintering and / or the second sintering helps to reduce side reactions, thereby better preparing the first lithium iron phosphate salt particles of the present application. Furthermore, in the conventional high-temperature sintering process, the carbon coating layer on the surface of the particles is prone to cracking, reducing the integrity of the carbon coating. The present application performs large particle synthesis at low temperature, which is conducive to improving the consistency and uniformity of the surface carbon coating.
[0171] In some embodiments, the first lithium iron phosphate salt particles are mainly obtained by the following preparation method:
[0172] Providing raw materials containing at least a lithium source, an iron source, a phosphorus source, a carbon source, a carbon film-forming agent, and a modifier, and performing at least two sintering steps, wherein:
[0173] The carbon content of the material after the first sintering is 0.01 wt%-0.79 wt%, optionally 0.05 wt%-0.4 wt%;
[0174] The carbon content of the material after the second sintering is 0.8 wt % to 2.0 wt %, and can be optionally 1.0 wt % to 1.6 wt %.
[0175] In some embodiments, the carbon content of the material after the first sintering can be 0.01 weight%, 0.05 weight%, 0.1 weight%, 0.15 weight%, 0.20 weight%, 0.25 weight%, 0.30 weight%, 0.35 weight%, 0.40 weight%, 0.45 weight%, 0.50 weight%, 0.55 weight%, 0.60 weight%, 0.65 weight%, 0.70 weight%, 0.75 weight%, 0.79 weight, or a range consisting of any two of the above carbon contents or a value in this range; the carbon content of the material after the second sintering can be 0.8 weight%, 0.9 weight%, 1.0 weight%, 1.1 weight%, 1.2 weight%, 1.3 weight%, 1.4 weight%, 1.5 weight%, 1.6 weight%, 1.7 weight%, 1.8 weight%, 1.9 weight%, 2.0 weight, or a range consisting of any two of the above carbon contents or a value in this range.
[0176] In the preparation method of the embodiment of the present application, adding a carbon source before the first sintering can effectively reduce the trivalent iron in the raw material, thereby improving the purity and stability of the product. Further, by controlling the temperature of the first sintering and the carbon content of the intermediate after the first sintering within the above range, it is helpful to increase the primary particle size of the first lithium iron phosphate salt particle precursor obtained after the first sintering. Specifically, during the first sintering process, the lower carbon content is conducive to reducing the barrier effect of the carbon layer on the growth process of the first lithium iron phosphate particles, which is conducive to the crystal growth of the first lithium iron phosphate salt particle precursor at a lower temperature. At the same time, it is also conducive to the solid-phase diffusion reaction between the modifier that may be added and the first lithium iron phosphate salt material, thereby facilitating the modification of metal ions at a higher concentration. By controlling the temperature of the second sintering and the carbon content of the sintered material within the above range, it is helpful to better coat the carbon on the surface of the first lithium iron phosphate salt particles to form a uniform and dense carbon coating layer, which is conducive to improving the surface conductivity of the first lithium iron phosphate particles, and improving its kinetic properties and gram capacity.
[0177] In some embodiments, a raw material containing at least a lithium source, an iron source, a phosphorus source, a carbon source, a modifier, and a carbon film-forming agent is provided, and sintering is performed at least twice.
[0178] In some embodiments, the mixing ratio of the lithium source, the iron source, and the phosphorus source satisfies, based on the atomic mole number of each element, Fe:P=(0.96-0.985):1, Li:Fe=(1.0-0.95):1.1.
[0179] In some embodiments, the mixing ratio of the iron source and the phosphorus source, calculated on the basis of the atomic moles of each element, satisfies Fe:P=0.96:1, Fe:P=0.965:1, Fe:P=0.97:1, Fe:P=0.975:1, Fe:P=0.98:1 or Fe:P=0.985:1.
[0180] In some embodiments, the mixing ratio of the lithium source and the iron source, calculated on the basis of the atomic moles of each element, satisfies Li:Fe=1.0:1.1, Li:Fe=0.99:1.1, Li:Fe=0.98:1.1, Li:Fe=0.97:1.1, Li:Fe=0.96:1.1 or Li:Fe=0.95:1.1.
[0181] In some embodiments, the weight ratio of the carbon source to the carbon film-forming agent is (9-0.25): 1. In some embodiments, the weight ratio of the carbon source to the carbon film-forming agent may be 9:1, 8:1, 7:1, 6:1, 5:1, 4:1, 3:1, 2:1, 1:1, 0.8:1, 0.5:1 or 0.25:1.
[0182] In some embodiments, the lithium source is a lithium-containing compound. In some embodiments, the lithium source includes at least one of lithium dihydrogen phosphate, lithium oxalate, lithium carbonate, lithium oxide, lithium hydroxide, and lithium acetate. In some embodiments, the lithium source includes lithium carbonate.
[0183] In some embodiments, the iron source is an iron-containing compound. In some embodiments, the iron source includes at least one of ferric hydroxide, ferrous chloride, ferric oxide, ferric phosphate, ferric pyrophosphate, ferrous oxalate, iron powder, ferric nitrate, ferric oxide, and ferric oxyhydroxide. In some embodiments, the iron source includes ferric oxide.
[0184] In some embodiments, the phosphorus source is a phosphoric acid compound. In some embodiments, the phosphorus source includes at least one of phosphoric acid, ammonium dihydrogen phosphate, and diammonium hydrogen phosphate. In some embodiments, the phosphorus source includes phosphoric acid.
[0185] In some embodiments, the carbon source comprises at least one of citric acid, glucose, sucrose, starch, fructose, and lactose. In some embodiments, the carbon source comprises glucose.
[0186] In some embodiments, the carbon film-forming agent includes at least one of polyethylene glycol, polyaniline, polyacrylonitrile, polyvinyl pyrrolidone, and polyvinyl alcohol. In some embodiments, the carbon film-forming agent includes polyaniline.
[0187] In some embodiments, the modifier includes at least one of titanium dioxide, vanadium pentoxide, n-butyl titanate, ammonium metavanadate, niobium ethoxide, niobium oxalate, niobium pentoxide, magnesium hydroxide, and magnesium nitrate. In some embodiments, the modifier includes titanium dioxide.
[0188] By using the raw materials in the above ratio, it is advantageous to form the first lithium iron phosphate salt particles of the present application.
[0189] In some embodiments, the method for preparing the first lithium iron phosphate salt particles comprises the following steps:
[0190] The first pulverization is performed after the first sintering, and the second pulverization is performed after the second sintering, wherein:
[0191] The Dv50 of the product after the first pulverization is 300nm-1200nm, and can be optionally 400nm-1100nm;
[0192] The Dv50 of the product after the second pulverization is 500nm-5000nm, and can be optionally 700nm-2500nm.
[0193] In the present application, the term "Dv50" refers to the particle size corresponding to when the volume cumulative particle size distribution percentage in the particles reaches 50%.
[0194] In some embodiments, the Dv50 of the product after the first crushing can be 300nm, 400nm, 500nm, 600nm, 700nm, 800nm, 900nm, 1000nm, 1100nm, 1200nm, or a range consisting of the Dv50 of any two of the above products after the first crushing or a value within the range.
[0195] In some embodiments, the Dv50 of the product after the second crushing can be 500nm, 600nm, 700nm, 800nm, 900nm, 1000nm, 1100nm, 1200nm, 1300nm, 1400nm, 1500nm, 1700nm, 1900nm, 2000nm, 2300nm, 2500nm, 2700nm, 2900nm, 3000nm, 3200nm, 3400nm, 3600nm, 3800nm, 4000nm, 4200nm, 4400nm, 4600nm, 4800nm, 5000nm, or a range composed of the Dv50 of any two of the above products after the second crushing or a value in this range.
[0196] In some embodiments, the pulverization includes one or more of mechanical crushing, grinding, sand milling, and air flow crushing.
[0197] The Dv50 of the particles can be measured using methods and equipment commonly used in the art. As an example, it can be measured using a laser particle size analyzer (Malvern Master Size 3000) with reference to GB / T19077.1-2016.
[0198] Controlling the Dv50 of the product after the first pulverization within the above range is conducive to reducing the growth barrier effect of the added carbon source and the possibly added modifying elements on the first lithium iron phosphate salt particle precursor crystal, and is helpful to prepare a micron-sized lithium iron phosphate salt particle precursor. By controlling the Dv50 value of the product after the second pulverization within the above range, it is helpful to obtain the first lithium iron phosphate salt particles having the primary average particle size of the present application.
[0199] A second aspect of the present application provides a positive electrode sheet, which includes the positive electrode active material of the first aspect of the present application.
[0200] In some embodiments, the compaction density of the positive electrode sheet is 2.40 g / cm 3 -2.80g / cm 3 . A higher compaction density is beneficial to improving the energy density of secondary batteries.
[0201] In some embodiments, the compaction density of the positive electrode sheet is 2.50 g / cm 3 -2.70g / cm 3 .
[0202] In some embodiments, the positive electrode sheet includes a current collector and one or more positive electrode slurry layers disposed on the current collector, wherein at least one positive electrode slurry layer includes the positive electrode active material of the first aspect of the present application or the positive electrode active material prepared according to the method of the second aspect of the present application.
[0203] A third aspect of the present application provides a secondary battery, which includes the positive electrode sheet of the second aspect of the present application.
[0204] A fourth aspect of the present application provides an electrical device, comprising the secondary battery of the third aspect of the present application.
[0205] In addition, the secondary battery and the electric device of the present application will be described below with reference to the drawings as appropriate.
[0206] In one embodiment of the present application, a secondary battery is provided.
[0207] Generally, a secondary battery includes a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator. During the battery charging and discharging process, active ions are embedded and released back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting ions between the positive electrode sheet and the negative electrode sheet. The separator is set between the positive electrode sheet and the negative electrode sheet, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing ions to pass through.
[0208] [Positive electrode]
[0209] The positive electrode sheet includes a positive electrode current collector and a positive electrode film layer arranged on at least one surface of the positive electrode current collector, wherein the positive electrode film layer includes the positive electrode active material of the first aspect of the present application.
[0210] As an example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is disposed on any one or both of the two opposite surfaces of the positive electrode current collector.
[0211] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0212] In some embodiments, the positive electrode film layer may further optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.
[0213] In some embodiments, the positive electrode film layer may further include a conductive agent, which may include, for example, at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0214] In some embodiments, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.
[0215] [Negative electrode]
[0216] The negative electrode sheet includes a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode film layer includes a negative electrode active material.
[0217] As an example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.
[0218] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, copper foil may be used. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0219] In some embodiments, the negative electrode active material may adopt the negative electrode active material for the battery known in the art. As an example, the negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, lithium titanate, etc. The silicon-based material may be selected from at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may be selected from at least one of elemental tin, tin oxide compounds, and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.
[0220] In some embodiments, the negative electrode film layer may further include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS).
[0221] In some embodiments, the negative electrode film layer may further include a conductive agent, which may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.
[0222] In some embodiments, the negative electrode film layer may optionally include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).
[0223] In some embodiments, the negative electrode sheet can be prepared in the following manner: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.
[0224] [Electrolytes]
[0225] The electrolyte plays the role of conducting ions between the positive electrode and the negative electrode. The present application has no specific restrictions on the type of electrolyte, which can be selected according to needs. For example, the electrolyte can be liquid, gel or all-solid.
[0226] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.
[0227] In some embodiments, the electrolyte salt can be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorodioxalatophosphate, and lithium tetrafluorooxalatophosphate.
[0228] In some embodiments, the solvent can be selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane sulfone, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.
[0229] In some embodiments, the electrolyte may further include additives, such as negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc.
[0230] [Isolation film]
[0231] In some embodiments, the secondary battery further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical stability and mechanical stability can be selected.
[0232] In some embodiments, the material of the isolation membrane can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane can be a single-layer film or a multi-layer composite film, without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.
[0233] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator may be formed into an electrode assembly by a winding process or a lamination process.
[0234] In some embodiments, the secondary battery may include an outer package, which may be used to encapsulate the electrode assembly and the electrolyte.
[0235] In some embodiments, the outer packaging of the secondary battery may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the secondary battery may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, and examples of the plastic include polypropylene, polybutylene terephthalate, and polybutylene succinate.
[0236] The present application has no particular limitation on the shape of the secondary battery, which may be cylindrical, square or any other shape. Figure 2 The secondary battery 5 is a square structure as an example.
[0237] In some embodiments, reference Figure 3 , the outer packaging may include a shell 51 and a cover plate 53. Among them, the shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can form an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. The number of electrode assemblies 52 contained in the secondary battery 5 can be one or more, and those skilled in the art can select according to specific actual needs.
[0238] In some embodiments, secondary batteries may be assembled into a battery module. The number of secondary batteries contained in the battery module may be one or more, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery module.
[0239] FIG. 4 is a battery module 4 as an example. Figure 4 In the battery module 4, the plurality of secondary batteries 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of secondary batteries 5 may be fixed by fasteners.
[0240] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of secondary batteries 5 are received in the receiving space.
[0241] In some embodiments, the battery modules described above may also be assembled into a battery pack. The battery pack may contain one or more battery modules, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery pack.
[0242] Figure 5 and Figure 6 1 is a battery pack 1 as an example. Figure 5 and Figure 6 The battery pack 1 may include a battery box and a plurality of battery modules 4 disposed in the battery box. The battery box includes an upper box body 2 and a lower box body 3. The upper box body 2 can cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 can be arranged in the battery box in any manner.
[0243] In addition, the present application also provides an electrical device, which includes at least one of the secondary battery, battery module, or battery pack provided in the present application. The secondary battery, battery module, or battery pack can be used as a power source for the electrical device, and can also be used as an energy storage unit for the electrical device. The electrical device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto.
[0244] As the electrical device, a secondary battery, a battery module or a battery pack may be selected according to its usage requirements.
[0245] Figure 7The power consumption device is taken as an example. The power consumption device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. In order to meet the high power and high energy density requirements of the power consumption device for the secondary battery, a battery pack or a battery module can be used.
[0246] Another example of a device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is usually required to be thin and light, and a secondary battery may be used as a power source.
[0247] Example
[0248] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.
[0249] 1. Preparation method
[0250] Example 1
[0251] (1) Preparation of positive electrode slurry:
[0252] Preparation of the first lithium iron phosphate salt particles:
[0253] Weigh lithium carbonate, ferric oxide, phosphoric acid, glucose, titanium dioxide (based on the total weight of lithium iron phosphate particles, the amount of titanium dioxide added is such that the titanium content in the prepared lithium iron phosphate particles is 5000ppm) and polyaniline, wherein the weight ratios of Li element, Fe element and P element are such that Fe:P=0.968:1, Li:Fe=1:0.98, and the weight ratio of glucose to polyaniline is such that glucose:polyaniline=1:2. The amount of glucose added is such that after the first sintering is completed, the carbon content accounts for 0.15% of the weight of the lithium iron phosphate precursor. Add water to the above substances to obtain a mixture slurry.
[0254] Use a ball mill to mix the mixture slurry evenly, grind it with a sand mill to obtain a slurry with a solid content of 38% and a Dv50 of 0.40μm, and spray dry it (the negative pressure of the high-speed spray dryer is -650~-200Pa, the inlet temperature is 300℃~360℃, and the outlet temperature is 100℃~140℃). The dried reactants are loaded into a sintering furnace for the first sintering, and the heating rate is controlled at 5℃ / min, the insulation temperature is controlled at 650℃, and the insulation time is 4h. After the material is cooled, it is crushed by a mechanical mill to obtain a powder.
[0255] Glucose as a carbon source and polyaniline as a carbon film-forming agent are added to the obtained powder, and then mixed with water to obtain a material with a solid content of 40%. Among them, the amount of glucose and polyaniline added satisfies that the carbon content of the product after the second sintering is 1.2% (based on the total weight of the lithium iron phosphate salt particles), and the weight ratio of glucose to polyaniline satisfies glucose: polyaniline = 1:2. The slurry is obtained by ball milling and sand milling, and the Dv50 of the insoluble matter in the slurry is 550nm. Spray drying is performed (the negative pressure of the high-speed spray dryer is -650 to -200Pa, the inlet temperature is 300℃ to 360℃, and the outlet temperature is 100℃ to 140℃). The dried reactants are loaded into a sintering furnace for a second low-temperature sintering (the heating rate is controlled at 5℃ / min, the sintering temperature is 750℃, and the sintering time is 4h). After the material is cooled, it is crushed for the second time to an average particle size of 870 nm. After demagnetization, lithium iron phosphate salt particles are obtained, with a carbon content of 1.2% and a Ti content of 5000 ppm in the lithium iron phosphate salt particles.
[0256] The first lithium iron phosphate salt particles and the second lithium iron phosphate salt particles (purchased from Guangdong Bangpu Recycling Technology Co., Ltd., item number BP-LFP-101) are blended according to the weight listed in Table 1 to obtain a positive electrode active material, and the above-blended positive electrode active material, conductive agent conductive carbon black, binder polyvinylidene fluoride and dispersant PVP are mixed in a weight percentage of 93:4.0:2.5:0.5 and N-methylpyrrolidone is added, and the mixture is fully mixed, stirred, and dispersed to form a positive electrode slurry.
[0257] (2) Preparation of positive electrode sheet:
[0258] The viscosity of the mixed and stirred slurry is adjusted to 8000-20000mPa.s until the slurry is not stratified, and the slurry is coated with 420mg / 1540mm by double-sided double-control coating equipment. 2 It is coated on the surface of the Al foil substrate, and then dried, cold pressed, cut and sliced to finally obtain the positive electrode sheet.
[0259] (3) Preparation of negative electrode sheet:
[0260] Artificial graphite, conductive carbon black, binder styrene-butadiene rubber (SBR) and thickener sodium carboxymethyl cellulose (CMC) were mixed evenly according to a weight percentage of 95:1.0:2.0:2.0, and deionized water was added. After stirring and dispersion, a negative electrode slurry was obtained. The negative electrode slurry was prepared at 211 mg / 1540 mm 2 It is coated on the Cu foil substrate, and then dried, cold pressed, cut and sliced to obtain the negative electrode sheet;
[0261] (4) Preparation of batteries:
[0262] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order. The separator should be able to isolate the positive and negative electrodes. The bare cell is obtained by winding. The bare cell is placed in an outer package, and the electrolyte is injected. After packaging, formation, exhaust and other processes, a lithium-ion battery is finally obtained.
[0263] Example 2
[0264] The difference between Example 2 and Example 1 is that the average particle size of the first lithium iron phosphate salt particles is 500 nm and the specific surface area is 7 m 2 / g, the Dv50 of the product after the first crushing is 350nm, and the Dv50 of the product after the second crushing is 800nm.
[0265] Example 3
[0266] The difference between Example 3 and Example 1 is that the primary average particle size of the first lithium iron phosphate salt particles is 3000nm and the specific surface area is 5m 2 / g, the Dv50 of the product after the first crushing is 1200nm, and the Dv50 of the product after the second crushing is 3200nm.
[0267] Example 4
[0268] The difference between Example 4 and Example 1 is that the primary average particle size of the second lithium iron phosphate salt particles is 150 nm and the specific surface area is 14.9 m 2 / g, and a carbon content of 1.4% by weight. The second lithium iron phosphate salt particles were purchased from Guangdong Brunp Recycling Technology Co., Ltd. with a product number of BP-LFP-102.
[0269] Example 5
[0270] The difference between Example 5 and Example 1 is that the primary average particle size of the second lithium iron phosphate salt particles is 480 nm and the specific surface area is 12.1 m 2 / g, and a carbon content of 1.2% by weight. The second lithium iron phosphate salt particles were purchased from Guangdong Brunp Recycling Technology Co., Ltd. with a product number of BP-LFP-103.
[0271] Example 6
[0272] The difference between Example 6 and Example 1 is that the weight ratio of the first lithium iron phosphate salt particles to the first lithium iron phosphate salt particles is 3:7.
[0273] Example 7
[0274] The difference between Example 7 and Example 1 is that the weight ratio of the first lithium iron phosphate salt particles to the first lithium iron phosphate salt particles is 7:3.
[0275] Example 8
[0276] The difference between Example 8 and Example 1 is that the weight ratio of the first lithium iron phosphate salt particles to the first lithium iron phosphate salt particles is 1:9.
[0277] Example 9
[0278] The difference between Example 9 and Example 1 is that the weight ratio of the first lithium iron phosphate salt particles to the first lithium iron phosphate salt particles is 9:1.
[0279] Example 10
[0280] The difference between Example 10 and Example 1 is that the titanium content of the first lithium iron phosphate salt particles is 2500 ppm, the first sintering temperature is 620°C, and the second sintering temperature is 720°C.
[0281] Embodiment 11
[0282] The difference between Example 11 and Example 1 is that the titanium content of the first lithium iron phosphate salt particles is 6000 ppm, the first sintering temperature is 655°C, and the second sintering temperature is 755°C.
[0283] Example 12
[0284] The difference between Example 12 and Example 1 is that vanadium pentoxide is used instead of titanium dioxide, and the carbon content after the first sintering is 0.15 weight %.
[0285] Embodiment 13
[0286] The difference between Example 13 and Example 1 is that niobium pentoxide is used instead of titanium dioxide, and the carbon content after the first sintering is 0.15 weight %, and the carbon content after the second sintering is 1.0 weight %.
[0287] Embodiment 14
[0288] The difference between Example 14 and Example 1 is that the primary average particle size of the second lithium iron phosphate salt particles is 450 nm and the specific surface area is 12.5 m 2 / g, and a carbon content of 1.2% by weight. The second lithium iron phosphate salt particles were purchased from Guangdong Brunp Recycling Technology Co., Ltd. with a product number of BP-LFP-104.
[0289] Embodiment 15
[0290] The difference between Example 15 and Example 1 is that the primary average particle size of the second lithium iron phosphate salt particles is 210 nm and the specific surface area is 14 m 2 / g, and the carbon content is 1.4% by weight. The second lithium iron phosphate salt particles were purchased from Guangdong Brunp Recycling Technology Co., Ltd. with the item number BP-LFP-105.
[0291] Example 16
[0292] The difference between Example 16 and Example 1 is that the carbon content is adjusted to 0.8 wt % so that the specific surface area of the first lithium iron phosphate salt particles is 3 m 2 / g.
[0293] Embodiment 17
[0294] The difference between Example 17 and Example 1 is that the carbon content is adjusted to 1.4 wt % so that the specific surface area of the first lithium iron phosphate salt particles is 8 m 2 / g.
[0295] Embodiment 18
[0296] The difference between Example 18 and Example 1 is that the primary average particle size of the first lithium iron phosphate is 650nm, and the BET is 6.5nm. 2 / g, carbon content is 1.2 wt%.
[0297] Embodiment 19
[0298] The difference between Example 19 and Example 1 is that the primary average particle size of the first lithium iron phosphate is 2500nm, and the BET is 5.5m 2 / g, and the carbon content is 1.2% by weight.
[0299] Embodiment 20
[0300] The difference between Example 20 and Example 1 is that the primary average particle size of the second lithium iron phosphate salt particles is 120 nm and the specific surface area is 15.5 m 2 / g, and a carbon content of 1.45% by weight. The second lithium iron phosphate salt particles were purchased from Guangdong Brunp Recycling Technology Co., Ltd. with a product number of BP-LFP-108.
[0301] Embodiment 21
[0302] The difference between Example 21 and Example 1 is that the primary average particle size of the second lithium iron phosphate salt particles is 600 nm and the specific surface area is 11.8 m 2 / g, and a carbon content of 1.2% by weight. The second lithium iron phosphate salt particles were purchased from Guangdong Brunp Recycling Technology Co., Ltd. with a product number of BP-LFP-109.
[0303] Comparative Example 1
[0304] The difference between Comparative Example 1 and Example 1 is that the first lithium iron phosphate salt particles are not included.
[0305] Comparative Example 2
[0306] The difference between Comparative Example 2 and Example 1 is that the carbon content of the product after the first sintering is controlled to be 1.1% by weight, the primary average particle size of the first lithium iron phosphate salt particles is 300 nm, and the specific surface area is 13 m 2 / g, the Dv50 of the product after the first crushing is 550nm, and the Dv50 of the product after the second crushing is 1200nm.
[0307] Comparative Example 3
[0308] The difference between Comparative Example 3 and Example 1 is that after the first sintering, the Dv50 of the crushed product is adjusted to 1.4 μm, the primary average particle size of the first lithium iron phosphate salt particles is 4000 nm, and the specific surface area is 6 m 2 / g, the Dv50 of the product after the first crushing is 550nm, and the Dv50 of the product after the second crushing is 1200nm.
[0309] Comparative Example 4
[0310] The difference between Comparative Example 4 and Example 1 is that the primary average particle size of the second lithium iron phosphate salt particles is 100 nm and the specific surface area is 16 m 2 / g, and a carbon content of 1.5% by weight. The second lithium iron phosphate salt particles were purchased from Guangdong Brunp Recycling Technology Co., Ltd. with a product number of BP-LFP-106.
[0311] Comparative Example 5
[0312] The difference between Comparative Example 5 and Example 1 is that the primary average particle size of the second lithium iron phosphate salt particles is 800 nm and the specific surface area is 11.5 m 2 / g, and a carbon content of 1.25% by weight. The second lithium iron phosphate salt particles were purchased from Guangdong Brunp Recycling Technology Co., Ltd. with a product number of BP-LFP-107.
[0313] 2. Battery performance test
[0314] 1) Primary average particle size
[0315] The pole piece is cut open perpendicularly to the large surface of the pole piece by an argon ion beam to expose the cross section, which is photographed by a scanning electron microscope, and the longest diameter of the lithium iron phosphate salt particles is statistically analyzed by the long diameter statistical method. Among them, the "primary average particle size" refers to the average value of the primary particle size of all particles, which is numerically equal to the total particle size value divided by the total number of particles. Among them, the primary particle size in the cross-section diagram refers to the longest distance connected by two points on the edge. Specifically, the total number of lithium iron phosphate salt particles with a primary particle size greater than 50nm and the primary particle size of lithium iron phosphate salt particles with a primary particle size greater than 50nm can be counted in the electron microscope scanning photo, and the primary average particle size of the lithium iron phosphate salt particles = the primary particle size of the total lithium iron phosphate salt particles / the total number of lithium iron phosphate salt particles. Among them, in the above-mentioned particle size statistical process, particles with a primary average particle size less than or equal to 50nm are not included in the statistical range.
[0316] 2) Dv50
[0317] Referring to GB / T19077.1-2016, the Dv50 value of the lithium iron phosphate salt particles was measured using a laser particle size analyzer (Malvern Master Size 3000). In addition, the Dv10, Dv90, and Dv99 of the present application were also measured in the same manner.
[0318] 3) Specific surface area
[0319] The specific surface area was tested by gas adsorption method according to the GB / T19587-2017 test standard, as follows: lithium iron phosphate granular salt was taken as a sample, the sample tube was immersed in liquid nitrogen at -196°C, and the adsorption amount of nitrogen on the solid surface at different pressures was measured at a relative pressure of 0.05-0.30. The monolayer adsorption amount of the sample was obtained based on the BET multilayer adsorption theory and its formula, thereby calculating the specific surface area of the material.
[0320] 4) Carbon content
[0321] The first lithium iron phosphate salt particles / the second lithium iron phosphate salt particles are burned in a high-frequency induction furnace and then the carbon content is tested by infrared absorption method. The specific testing process is based on the standard GB / T20123-2006 / ISO 15350:2000.
[0322] 5) Content of Q element (eg Ti element) in the first lithium iron phosphate salt particles
[0323] The content of Q element in the first lithium iron phosphate salt particles is tested with reference to GB / T 33822-2017.
[0324] 6) Solid content of positive electrode slurry
[0325] Prepare an electronic balance (accuracy 0.0001), an oven, and a glass drying tray. Take 8-10g of the positive electrode slurry sample and spread it evenly on the sample tray, and record the mass of the slurry before drying as A. Cover the oven door and heat it. As the heating progresses, the temperature in the furnace continues to rise, rising to 130°C for 5 hours. After drying, cool it in the oven and take it out, record the mass of the slurry after drying, perform multiple drying, and record the mass after drying as B after the sample mass is constant. Slurry solid content = (A / B) × 100%.
[0326] 7) Pole compaction density
[0327] The "pole piece compaction density" referred to in this application refers to the "ultimate compaction density" of the pole piece, and the test method is as follows:
[0328] The double-sided coated electrode is cold pressed by a roller press to test the elongation of the electrode after cold pressing and to evaluate the flexibility of the electrode after cold pressing.
[0329] By increasing the pressure of the roller press, pole pieces with different compaction densities will be obtained. As the pressure increases, the compaction density of the pole piece increases, the elongation of the pole piece increases, and the flexibility of the pole piece decreases. Too high an elongation of the pole piece can easily cause the pole piece to warp, and too low a flexibility of the pole piece can easily cause the pole piece to break brittlely. Therefore, the smaller of the compaction density corresponding to the elongation of the pole piece of 6‰ or the number of times the pole piece's flexibility is folded 3 times is defined as the limit compaction density.
[0330] The compacted density is calculated by dividing the weight of the single-sided positive electrode film layer by the volume of the positive electrode film layer.
[0331] 8) The capacity ratio η of the first lithium iron phosphate particles in the embodiment and the comparative example when discharged to 3.2V and discharged to 2.0V respectively
[0332] First, prepare a button cell. The specific button cell preparation process is as follows: mix 2.0000g of the first lithium iron phosphate salt particles with 0.1111g of conductive carbon black and 0.1111g of polyvinylidene fluoride, and then add them to 2.5g of organic solvent N-methylpyrrolidone, and mix them thoroughly to form a slurry. The slurry is coated on aluminum foil with a coating thickness of 140 microns, vacuum dried at 120°C for 2h, and punched into a disc with a diameter of 13mm using a puncher. Use a tablet press to press the tablet at 10Mpa, and vacuum heat preservation at 120°C for 12h to obtain a positive electrode. Weigh the weight of the positive electrode, where the loading amount of the first lithium iron phosphate salt particles is 11-12mg. Button cells were assembled in an argon-protected glove box, with a metal lithium sheet as the negative electrode, an electrolyte of a 1:1 volume ratio of EC (ethylene carbonate) and DMC (1,2-dimethyl carbonate) mixed solvent, LiPF6 electrolyte, and a Celgard 2400 microporous polyethylene membrane as the separator.
[0333] The prepared button cell was tested for electrical performance on a blue electric tester. Specifically, the button cell was charged and discharged twice at a constant current of 0.1C within a voltage range of 2.0V to 3.75V, and then charged and discharged once at a constant current of 1C. In the charge and discharge test at a rate of 1C, the capacity value extracted when the discharge voltage was 3.2V was recorded as C1, and the capacity value extracted when discharged to 2.0V was recorded as C2, and η = C1 / C2. The charging process includes constant voltage charging, constant voltage of 3.75V, and constant voltage cut-off current of 50μA.
[0334] 9) The capacity ratios η of the positive electrode active materials in the embodiment and the comparative example when discharged to 3.2 V and when discharged to 2.0 V, respectively
[0335] First, a button cell is prepared. The specific button cell preparation process is as follows: 2.0000g of the positive electrode active material in the embodiment and the comparative example (a blend of the first lithium iron phosphate salt particles and the second lithium iron phosphate salt particles) is mixed with 0.1111g of conductive carbon black and 0.1111g of polyvinylidene fluoride, and then added to 2.5g of organic solvent N-methylpyrrolidone, and mixed thoroughly to form a slurry. The slurry is coated on aluminum foil with a coating thickness of 140 microns, vacuum dried at 120°C for 2h, and punched into a disc with a diameter of 13mm using a puncher. Use a tablet press to press the tablet at 10Mpa, and vacuum heat preservation at 120°C for 12h to obtain a positive electrode sheet. Weigh the weight of the positive electrode sheet, where the loading amount of the positive active material is 11-12mg. Button cells were assembled in an argon-protected glove box, with a metal lithium sheet as the negative electrode, an electrolyte of a 1:1 volume ratio of EC (ethylene carbonate) and DMC (1,2-dimethyl carbonate) mixed solvent, LiPF6 electrolyte, and a Celgard 2400 microporous polyethylene membrane as the separator.
[0336] The prepared button cell was tested for electrical performance on a blue electric tester. Specifically, the button cell was charged and discharged twice at a constant current of 0.1C within a voltage range of 2.0V to 3.75V, and then charged and discharged once at a constant current of 1C. In the charge and discharge test at a rate of 1C, the capacity value extracted when the discharge voltage was 3.2V was recorded as C1, and the capacity value extracted when discharged to 2.0V was recorded as C2, and η = C1 / C2. The charging process includes constant voltage charging, constant voltage of 3.75V, and constant voltage cut-off current of 50μA.
[0337] 10) DCR (10% SOC)
[0338] The DCR (10% SOC) data in this application can reflect the power performance, and the test method is as follows:
[0339] Capacity calibration: After the lithium ion batteries prepared in the embodiments and comparative examples were kept at 25°C for 2 hours, they were charged to 3.65V at a constant current of 0.33C, and then charged to 0.05C at a constant voltage of 3.65V. After the charging was completed, the tested batteries were kept at 25°C for 2 hours, and then discharged to 2.5V at a direct current of 0.33C, and the discharge capacity at room temperature was recorded as C0;
[0340] Adjust SOC (battery state of charge): After keeping the calibrated lithium-ion battery at 25°C for 2 hours, discharge it at a 1 / 3C0 discharge rate for 144 minutes to adjust the lithium-ion battery capacity to 10% SOC;
[0341] Power test: After the 10% SOC lithium-ion battery is left to stand at 25°C for 2h, it is discharged at a discharge rate of 3C0 for 30s under a pulse current I. The voltage before 3C0 discharge is recorded as V1, and the voltage at the end of 30s discharge is recorded as V2. The value of the DC internal resistance (V1-V2) / I is calculated. This data can be used to characterize the power performance of the battery.
[0342] III. Analysis of test results of various embodiments and comparative examples
[0343] The batteries of the embodiments and comparative examples were prepared according to the above methods, and various performance parameters were measured. The parameters of the positive electrode active material are shown in Table 1, and the performance test results are shown in Table 2.
[0344]
[0345] Table 2: Performance test results
[0346] Examples Slurry solid content <![CDATA[The compaction density of the electrode sheet (g / cm 3 )]]> η(%) DCR (10% SOC) Example 1 57.0 2.70 90.0 1329 Example 2 56.5 2.55 92.0 1308 Example 3 58.0 2.60 89.0 1351 Example 4 55.0 2.60 91.0 1296 Example 5 58.0 2.65 88.0 1391 Example 6 56.0 2.65 89.0 1349 Example 7 58.0 2.65 91.0 1263 Example 8 55.0 2.60 88.0 1392 Example 9 60.0 2.52 91.5 1220 Example 10 57.0 2.70 89.0 1352 Embodiment 11 57.0 2.70 91.0 1298 Example 12 57.0 2.70 90.0 1325 Embodiment 13 57.0 2.70 90.0 1331 Embodiment 14 57.5 2.65 89.0 1358 Embodiment 15 55.5 2.65 90.5 1312 Example 16 58.0 2.65 87.0 1371 Embodiment 17 56.5 2.65 92.5 1303 Embodiment 18 56.8 2.60 91.0 1318 Embodiment 19 57.5 2.63 89.5 1345 Embodiment 20 54.0 2.55 91.2 1288 Embodiment 21 59.0 2.50 87.0 1430 Comparative Example 1 55.0 2.40 82.0 1680 Comparative Example 2 55.5 2.42 93.0 1280 Comparative Example 3 59.0 2.45 87.6 1408 Comparative Example 4 50.0 2.42 91.5 1312 Comparative Example 5 59.5 2.44 86.0 1570
[0347] According to the above results, the positive electrode active materials in Examples 1-21 all include first lithium iron phosphate salt particles and second lithium iron phosphate salt particles, wherein the primary average particle size of the first lithium iron phosphate salt particles is 500-3000nm, and the primary average particle size of the second lithium iron phosphate salt particles is 120-600nm. From the comparison between Examples 1-21 and Comparative Examples 1-5, it can be seen that the positive electrode sheet containing the positive electrode active material has a higher compaction density, and the battery containing the positive electrode sheet has a higher power performance.
[0348] The positive electrode active material of Example 19 was tested using a ZEISS sigma 300 scanning electron microscope and then tested according to the standard JY / T010-1996. The morphology of the sample was observed. The observation results are shown in Figure 1 .Depend on Figure 1 It can be seen that the first lithium iron phosphate particles and the second lithium iron phosphate salt particles are mixed evenly, and the second lithium iron phosphate salt particles densely fill the pores of the first lithium iron phosphate particles.
[0349] From the comparison between Examples 1, 4-5, 14-15 and Examples 20-21, it can be seen that when the primary average particle size of the second lithium iron phosphate salt particles is 150-480 nm, the positive electrode sheet containing the positive electrode active material has a higher compaction density.
[0350] From the comparison between Examples 1, 6-7 and 8-9, it can be seen that when the weight ratio of the first lithium iron phosphate salt particles to the second lithium iron phosphate salt particles is 3:7-7:3, the positive electrode sheet containing the positive electrode active material has a higher compaction density.
[0351] From the comparison of Example 1, Example 6-7, Example 9 and Example 8, it can be seen that when the weight ratio of the first lithium iron phosphate salt particles to the second lithium iron phosphate salt particles is 3:7-9:1, the positive electrode slurry containing the positive electrode active material has a higher solid content, the button cell containing the positive electrode active material has a higher η value, and the battery containing the positive electrode active material has a lower DCR (10% SOC), reflecting that the battery has better kinetic performance and higher power performance.
[0352] From the comparison between Example 1, Example 7, Example 9 and Example 6, Example 8, it can be seen that when the weight ratio of the first lithium iron phosphate salt particles to the second lithium iron phosphate salt particles is 4:6-9:1, the positive electrode slurry containing the positive electrode active material has a higher solid content, the button cell containing the positive electrode active material has a higher η value, and the battery containing the positive electrode active material has a lower DCR (10% SOC), reflecting that the battery has better kinetic performance and higher power performance.
[0353] From the comparison between Example 7 and Example 9 and Example 1, Example 6 and Example 8, it can be seen that when the weight ratio of the first lithium iron phosphate salt particles to the second lithium iron phosphate salt particles is 7:3-9:1, the positive electrode slurry containing the positive electrode active material has a higher solid content, the button cell containing the positive electrode active material has a higher η value, and the battery containing the positive electrode active material has a lower DCR (10% SOC), reflecting that the battery has better kinetic performance and higher power performance.
[0354] From the comparison between Example 1, Example 11 and Example 10, it can be seen that, calculated based on the total weight of the first lithium iron phosphate salt particles, when the Ti content in the first lithium iron phosphate salt particles is 5000-6000ppm, the button battery containing the positive electrode active material has a higher η value, and the battery containing the positive electrode active material has a lower DCR (10% SOC), reflecting that the battery has better kinetic performance and higher power performance.
[0355] From the comparison between Example 1, Example 17 and Example 16, it can be seen that when the specific surface area of the first lithium iron phosphate salt particles is 6m2 / g-8m 2 / g, the button cell containing the positive electrode active material has a higher η value, and the battery containing the positive electrode active material has a lower DCR (10% SOC), which reflects that the battery has better kinetic performance and higher power performance.
[0356] From the comparison between Example 1, Example 17 and Example 16, it can be seen that, calculated based on the total weight of the first lithium iron phosphate salt particles, the carbon content of the first lithium iron phosphate salt particles is Cx1 weight %, when 1.2≤Cx1≤1.4, the button battery containing the positive electrode active material has a higher η value, and the battery containing the positive electrode active material has a lower DCR (10% SOC), reflecting that the battery has better kinetic performance and higher power performance.
[0357] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A positive electrode active material, comprising first lithium iron phosphate salt particles and second lithium iron phosphate salt particles, wherein the first lithium iron phosphate salt particles have an average primary particle size of 500-3000 nm, and the second lithium iron phosphate salt particles have an average primary particle size of 120-600 nm. 2 . The positive electrode active material according to claim 1 , wherein a weight ratio of the first lithium iron phosphate salt particles to the second lithium iron phosphate salt particles is 1:9-9:
1.
3. The positive electrode active material according to claim 1 or 2, wherein the first lithium iron phosphate salt particles have a molecular formula of Li m1 Fe x1 P y1 O j1 Q1 q1 , wherein Q1 includes at least one of Al, Na, K, Mg, Cu, Mn, Cr, Zn, Pb, Ca, Co, Ni, Sr, Nb, V, Ti, B, S, Si, N, F, Cl, Br, 0.95≤m1≤1.15, 0.9≤x1≤1, 0.95≤y1≤1, 3.5≤j1≤4, 0<q1≤0.1, and / or The second lithium iron phosphate salt particles have a molecular formula of Li m2 Fe x2 P y2 O j2 Q2 q2 , wherein Q2 includes at least one of Al, Na, K, Mg, Cu, Mn, Cr, Zn, Pb, Ca, Co, Ni, Sr, Nb, V, Ti, B, S, Si, N, F, Cl, and Br, 0.95≤m2≤1.15, 0.9≤x2≤1, 0.95≤y2≤1, 3.5≤j2≤4, and 0≤q2≤0.
1.
4. The positive electrode active material according to claim 3, wherein in the first lithium iron phosphate salt particles, the Q1 includes at least one of Ti, V, Mg, and Nb, and the content of Ti, V, Mg, and / or Nb is 1000-10000 ppm based on the total weight of the first lithium iron phosphate salt particles.
5. The positive electrode active material according to any one of claims 1 to 4, wherein the specific surface area of the first lithium iron phosphate salt particles is 3 m 2 / g-8m 2 / g.
6. The positive electrode active material according to any one of claims 1 to 5, wherein the carbon content of the first lithium iron phosphate salt particles is Cx1% by weight, based on the total weight of the first lithium iron phosphate salt particles, wherein: 0.8≤Cx1≤2.
0. 7 . The positive electrode active material according to claim 1 , wherein the primary average particle size of the first lithium iron phosphate salt particles is 650-2500 nm.
8. The positive electrode active material according to any one of claims 1 to 7, wherein the capacity ratio of the first lithium iron phosphate salt particles is η≥88%, wherein η is defined as: The battery using the first lithium iron phosphate salt particles as the positive electrode active material is charged and discharged twice at a constant current rate of 0.1C in the voltage range of 2.0V to 3.75V, and then charged and discharged once at a constant current rate of 1C. In the charge and discharge test at the rate of 1C, the capacity value extracted at a discharge voltage of 3.2V is recorded as C1, and the capacity value extracted and discharged to 2.0V is C2, and η=C1 / C2, wherein, The charging process includes constant voltage charging, constant voltage 3.75V, constant voltage cut-off current 50μA.
9. The positive electrode active material according to any one of claims 1 to 8, wherein the first lithium iron phosphate salt particles satisfy at least one of (a) to (f): (a) Dv10 of the first lithium iron phosphate salt particles is ≥ 0.2 μm; (b) the Dv50 of the first lithium iron phosphate particles is 0.5-5 μm; (c) Dv90 of the first lithium iron phosphate salt particles is ≤10 μm; (d) Dv99 of the first lithium iron phosphate salt particles is ≤12 μm; (e) The powder compaction density of the first lithium iron phosphate salt under a pressure of 3 tons is ≥ 2.25 g / cm 3 ; (f) The powder resistivity of the first lithium iron phosphate salt is less than 60Ω·cm.
10. The positive electrode active material according to any one of claims 1 to 9, wherein the specific surface area of the second lithium iron phosphate salt particles is 11 m 2 / g-16m 2 / g.
11. The positive electrode active material according to any one of claims 1 to 10, wherein the carbon content of the second lithium iron phosphate salt particles is Cx2 wt % calculated based on the total weight of the second lithium iron phosphate salt particles, wherein: 1.2≤Cx2≤1.
5. 12 . The positive electrode active material according to claim 1 , wherein the primary average particle size of the second lithium iron phosphate salt particles is 360-480 nm.
13. The positive electrode active material according to any one of claims 1 to 12, wherein the first lithium iron phosphate salt particles are mainly obtained by the following preparation method: Providing raw materials containing at least a lithium source, an iron source, a phosphorus source, a carbon film-forming agent, a carbon source, and a modifier, and performing at least two sintering steps, wherein: The temperature of the first sintering is 500℃-760℃; The temperature of the second sintering is 700℃-800℃.
14. The positive electrode active material according to claim 13, wherein the first lithium iron phosphate salt particles are mainly obtained by the following preparation method: Providing raw materials containing at least a lithium source, an iron source, a phosphorus source, a carbon source, a carbon film-forming agent, and a modifier, and performing at least two sintering steps, wherein: The carbon content of the material after the first sintering is 0.01 wt%-0.79 wt%; The carbon content of the material after the second sintering is 0.8 wt%-2.0 wt%.
15. The positive electrode active material according to claim 13 or 14, wherein the preparation method of the first lithium iron phosphate salt particles comprises the following steps: The first pulverization is performed after the first sintering, and the second pulverization is performed after the second sintering, wherein: The Dv50 of the product after the first crushing is 300nm-1200nm; The Dv50 of the product after the second pulverization is 500nm-5000nm. 16 . A positive electrode sheet, comprising the positive electrode active material according to claim 1 .
17. The positive electrode sheet according to claim 16, wherein the compaction density of the positive electrode sheet is 2.40 g / cm 3 -2.80g / cm 3 .
18. The positive electrode sheet according to claim 16 or 17, comprising a current collector and one or more positive electrode slurry layers disposed on the current collector, wherein at least one of the positive electrode slurry layers comprises the positive electrode active material according to any one of claims 1 to 15.
19. A secondary battery comprising the positive electrode sheet according to any one of claims 16 to 18.
20. An electric device comprising the secondary battery according to claim 19.
Citation Information
Patent Citations
Positive pole piece and preparation method and application thereof
CN113036085A
High-compaction-density lithium iron phosphate and preparation method thereof
CN113562714A
Lithium iron phosphate positive electrode active material, preparation method thereof, positive electrode plate and battery
CN114068919A
Secondary battery and preparation method thereof
CN115513515A
Lithium iron phosphate positive active material, positive pole piece and lithium ion battery
CN116646516A
Cited By
Lithium iron phosphate positive electrode material and preparation method thereof, positive plate and battery
CN120709358A
Lithium iron phosphate material and preparation method thereof, positive plate, battery, energy storage device and energy storage system
CN121035203A